Redesigning Healthcare Waqf: Key Characteristics and Strategic Models for Indonesia Using the Delphi–Likert Approach - Sulistyowati Sulistyowati; Ascarya Ascarya; Raditya Sukmana; Tatang Astarudin; Rodame Monitorir Napitupulu (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2025)
This study explores the essential characteristics of healthcare waqf and proposes context-appropriate models for implementation in Indonesia. Employing the Delphi method alongside a Likert scale, expert consensus validated 23 out of 31 proposed characteristics, with significant agreement indicated by Kendallâ€™s W. The identified healthcare waqf types include clinics, general hospitals, childrenâ€™s hospitals, and specialist hospitals. These institutions can be financed through a blend of Islamic social and commercial finance and managed by a subsidiary, third party, or nÄáº“ir (waqf manager). Based on these characteristics, four models are proposed: social, simple productive, innovative productive, and integrated social-productive healthcare waqf models. These models aim to provide accessible healthcare services for both underserved populations and the general public. While designed for Indonesia, the studyâ€™s methodological approach and conceptual framework can be adapted for application in other contexts. This research offers a novel foundation for developing effective, sustainable healthcare waqf initiatives.